Construction of a nomogram for predicting the prognosis of patients with cervical spondylotic myelopathy: a retrospective study - He Ling; Gaoyong Deng; Shaohuai Xia; Wencai Li; Rongbin Lu; Mingjian Lin; Zhao Huang (Scientific Reports)
Abstract Cervical spondylotic myelopathy (CSM) is a neurological disorder characterized by degenerative changes in the spinal cord and compression of the spinal cord and its adjacent structures due to various reasons, such as intervertebral disc herniation. The Japan Orthopaedic Association score is a disease-specific outcome tool that provides quantitative measurements for CSM patients. At present, no scholars have developed a model that can directly predict the prognosis of CSM patients. This study used binary logistic regression analysis to identify clinical independent predictive factors, and then used R language to construct a nomogram. The results showed that Hb (0.71 [0.51, 0.99]), LYM (0.32 [0.22, 0.46]), and ALB (0.32 [0.23, 0.45]) were independent predictive factors. Good prediction performance with modest errors was shown by the nomogram in both the training and validation groups. Hb, LYM, ALB are independent predictors of the prognosis of ACDF in CSM patients. The constructed nomogram can help clinicians assess and treat patients early, benefiting more patients.